2007
DOI: 10.1021/jp067107e
|View full text |Cite
|
Sign up to set email alerts
|

Electron Photodetachment from Iodide in Ionic Liquids through Charge-Transfer-to-Solvent Band Excitation

Abstract: Solvation of iodide and electrons in an ionic liquid (N,N,N-trimethyl-n-propylammonium bis(trifluoromethanesulfonyl)imide; TMPA-TFSI) was studied through the absorption spectra of the charge-transfer-to-solvent (CTTS) state of iodide and of solvated electrons. The interaction between the TMPA cation and iodide was strong, whereas electrons were weakly solvated in TMPA-TFSI. We followed electron photodetachment from iodide to the ionic liquid and formation of the solvated electrons by observing absorption in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
57
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 26 publications
8
57
0
Order By: Relevance
“…The absorption maxima are located at 1100 nm in all ionic liquids studied, which are similar to that observed in TMPA-TFSI as previously reported (Katoh et al, 2007). The similarity of the peak position implies that electrons in these ionic liquids are located in sites having similar chemical environments.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The absorption maxima are located at 1100 nm in all ionic liquids studied, which are similar to that observed in TMPA-TFSI as previously reported (Katoh et al, 2007). The similarity of the peak position implies that electrons in these ionic liquids are located in sites having similar chemical environments.…”
Section: Resultssupporting
confidence: 86%
“…We have recently studied solvated electron in trimethyl-propylammonium-bis(trifluoromethylsulfonyl)imide (TMPA-TFSI) produced by pulse radiolysis as well as photodetachment of iodide through charge-transfer-to-solvent (CTTS) band excitation (Katoh et al, 2007). The spectra obtained from the both methods were identical and broad absorption band peaking around 1100 nm.…”
Section: Introductionmentioning
confidence: 99%
“…At first, the smaller S values at very young positron ages were explained by the slower Ps formation [7] by referring the report indicating the excess electrons move freely for longer time [4]. However, detailed analysis of AMOC results, i.e.…”
Section: Introductionmentioning
confidence: 98%
“…Some researches indicated that the excess electrons in room temperature ionic liquids (RTILs) move freely for relatively long time [4].…”
Section: Introductionmentioning
confidence: 99%
“…28 Many fast bimolecular reactions have been studied in ILs. [29][30][31][32][33][34][35][36][37] In general, hydrodynamic approximation of the diffusion coefficient on the basis of the Stokes-Einstein equation is not applicable to diffusion-limited reactions in ILs. Several research groups have suggested that the faster translational diffusion in ILs is due to a large void volume produced by cations and anions.…”
Section: Introductionmentioning
confidence: 99%